Transcriptionally induced nucleoid-associated protein-like ccr1 in combined-culture serves as a global effector of Streptomyces secondary metabolism - Lei, Yukun; Onaka, Hiroyasu; Asamizu, Shumpei (Frontiers in Microbiology, 2024)
Combined-cultures involving mycolic acid-containing bacteria (MACB) can stimulate secondary metabolite (SM) production in actinomycetes. In a prior investigation, we screened Streptomyces coelicolor JCM4020 mutants with diminished production of SMs, specifically undecylprodigiosin (RED), which was enhanced by introducing the MACB Tsukamurella pulmonis TP-B0596. In this study, we conducted mutational analysis that pinpointed the sco1842 gene, which we assigned the gene name ccr1 (combined-culture related regulatory protein no. 1), as a crucial factor in the deficient phenotype observed in the production of various major SMs in S. coelicolor A3(2). Notably, the Ccr1 (SCO1842) homolog was found to be highly conserved throughout the Streptomyces genome. Although Ccr1 lacked conserved motifs, in-depth examination revealed the presence of a helix-turn-helix (HTH) motif in the Nterminal region and a helicase C-terminal domain (HCTD) motif in the C-terminal region in some of its homologs. Ccr1 was predicted to be a nucleoid-associated protein (NAP), and its impact on gene transcription was validated by RNA-seq analysis that revealed genome-wide variations. Furthermore, RT-qPCR demonstrated that ccr1 was transcriptionally activated in combined-culture with T. pulmonis, which indicated that Ccr1 is involved in the response to bacterial interaction. We then investigated Streptomyces nigrescens HEK616 in combinedculture, and the knockout mutant of the ccr1 homolog displayed reduced production of streptoaminals and 5aTHQs. This finding reveals that the Ccr1 homolog in Streptomyces species is associated with SM production. Our study elucidates the existence of a new family of NAP-like proteins that evolved in Streptomyces species and play a pivotal role in SM production.